7-(Pyrazol-4-yl)-3H-imidazo[4, 5-b]pyridine-based derivatives for kinase inhibition: Co-crystallisation studies with Aurora-A reveal distinct differences in the orientation of the pyrazole N1-substituent. Issue 19 (1st October 2015) - Bavetsias, Vassilios; Pérez-Fuertes, Yolanda; McIntyre, Patrick J.; Atrash, Butrus; Kosmopoulou, Magda; O'Fee, Lisa; Burke, Rosemary; Sun, Chongbo; Faisal, Amir; Bush, Katherine; Avery, Sian; Henley, Alan; et al.
Graphical abstract